Law on Radio Frequencies - The National Assembly (2009)
This Law provides for the management and use of radio frequencies, radio equip ment and satellite orbits and management of safety of radio radiation and electromagnetic compatibility (below collectively referred to as management and use of radio frequencies); rights and obligations of organizations and individuals involved in the management and use of radio frequencies.